Cope with non-collaboration situations in Pediatric Dentistry (Research, Society and Development, 2023)
Introduction: The behavior management strategies with children is part of the dentist's technique and behavioral planning. Different protocols recommend describing the same psychological strategies, but there are still few examples or discussions on how the dentist can proceed during clinical care. The present study sought, based on knowledge of reports from future professionals, examples of possible strategies that indicate ways of coping to help children during clinical routines. Objectives: The aim of the study was to analyze verbal reports of dental students related to coping with problem situations in pediatric dentistry.  Method: A qualitative study was conducted, in which the responded described his possible conduct in relation to children´s attendance.  The questionnaire had 10 questions and was applied to 101 dentistry students. Student responses were categorized in relation to each problem situation and management strategies. The answers were arranged as appropriate for the child care situations. Results: The data identified examples related to management in a three axes of analysis: 1.) Use of description, 2.) Professional posture and 3) Involvement of the child. Conclusion: The analysis of the hypothetical examples allowed a critical and dynamic reflection on the ways of caring for children in Pediatric Dentistry, in consonance with the principles of humanized care.